A hydrogel sealant for the treatment of severe hepatic and aortic trauma with a dissolution feature for post-emergent care. Issue 2 (5th January 2017) - Konieczynska, Marlena D.; Villa-Camacho, Juan C.; Ghobril, Cynthia; Perez-Viloria, Miguel; Blessing, William A.; Nazarian, Ara; Rodriguez, Edward K.; Grinstaff, Mark W.
Abstract : On-demand dissolvable hydrogel sealant reduces blood loss significantly in in vivo animal models of non-compressible hemorrhage. Abstract : Non-compressible hemorrhage is an important cause of pre-hospital death following trauma, and immediate control of blood loss is critical. An ideal material for hemorrhage management does not require manual pressure to control bleeding, does not rely on the natural clotting cascade, is suitable for intracavitary hemorrhage, and is removed without debridement. A dissolvable dendritic thioester hydrogel sealant is described for intracavitary wounds. The hydrogel is composed of a lysine-based dendron and a PEG-based crosslinker, which are synthesized in high yields and subsequently characterized by 1 H, 13 C NMR spectroscopy, and MALDI. The hydrogel dissolution relies on a thiol–thioester exchange mechanism. When compared to untreated controls, the application of the hydrogel sealant reduces blood loss by 33% in a rat model of severe hepatic hemorrhage (23.57 ± 8.27 mL kg −1 vs. 35.21 ± 7.47 mL kg −1 ; p = 0.02) and by 22% in a rat model of aortic injury (17.95 ± 3.84 mL kg −1 vs. 23.09 ± 3.80 mL kg −1 ; p = 0.03). A unique feature of the hydrogel is its dissolution with a biocompatible solution following initial application – thus the treated wound area can be re-exposed for definitive surgical care in an operative setting.